Assessment of awareness about cardiovascular disease risk factors and association between overweight and family history of cardiovascular disease among first-year medical students of a medical college in Karnataka - Amruth M, Sagorika Mullick; Balakrishna AG.; Prabhudeva MC. (Universiti Kebangsaan Malaysia, 2015)
Background: It is estimated in WHO Noncommunicable Diseases (NCD) Country Profiles 2011 that NCD account for 53% of all deaths. Of which, 24% are due to cardiovascular diseases (CVDs) alone. Lifestyle-related behavioral risk factors are mainly implicated among medical students. Objectives: To assess the awareness about CVD risk factors; to measure the cardiovascular risk behaviors using structured questionnaire; and to find the association between overweight and family history of CVDs among first-year medical students. Materials and Methods: A cross-sectional study was carried out among first-year medical students of Shridevi Institute of Medical Sciences & Research Hospital, Tumkur, Karnataka, India. A self-administered structured questionnaire was used to obtain information. The study period was from March 2014 to May 2014. The data analysis was done using SPSS software, version 17. w2-test and unpaired t-test were used. Results: The study subjects were 146 first-year medical students belonging to 17–22 year age group. There was lack of awareness about CVD risk factors. CVD risk behaviors were highly prevalent among medical students. Students with family history of CVDs had higher mean body mass index (22.61 vs 21.44 kg/m2, P o 0.05) than those without family history of CVDs. The association between overweight and family history of CVDs among students was statistically significant (P o 0.05). Conclusion: Lack of awareness about CVD risk factors and unhealthy behavioral practices are prevalent among first-year medical students and may progress as students advance through medical college. Behavior change communication and health education strategies are essential.